Copyright in a time of crisis - Morrison, Chris; Secker, Jane (Bobcatsss, 2023)
In March 2020, following the outbreak of the COVID-19 global pandemic, universities and schools around the world switched rapidly to online learning. In this talk, invited speakers Chris Morrison (University of Kent) and Jane Secker (City, University of London) will focus on the copyright and licensing issues that arose and the impact that they had on access to digital and print learning resources. The speakers will explain how issues associated with online learning point to the need for greater levels of copyright literacy, amongst educators and students. They argue that the pandemic could lead to a step change in the way in which content is produced and shared for teaching and learning, but only if those in education and research are able to critically examine the issues. In the first few months the shift to online learning, referred to as ‘’Emergency remote teaching” (Hodges et al, 2020) was largely an attempt allow students to progress with their studies. Libraries responded by trying to increase the number of digital resources available to support students studying remotely. Additionally, many publishers temporarily made a number of additional resources available for free. However, as the situation continued into the autumn, more sustained efforts were needed to plan for the new academic year and deliver high quality online teaching. As budgets across education became stretched, educators and librarians urgently considered the balance between maintaining access to existing collections and finding more sustainable solutions. The speakers’ experience suggests that copyright was a relatively low priority for many university lecturers and teachers prior to the pandemic. However, as experts in copyright and online learning (Secker and Morrison, 2016), and passionate advocates for greater levels of understanding of copyright (or copyright literacy), the speakers recognised that access to educational resources was likely to be an issue, as so few materials used in teaching are openly available (Gadd et al, 2019). In this presentation, they will discuss their response to the pandemic and highlight the actions of those in the copyright community to support online learning. They will also report on the increased traction that open educational practice has gained during this time. In March 2020, the speakers wrote a blog post reminding the education community about existing licences and copyright exceptions that support online learning, and also the wealth of open educational resources available. They also wrote and spoke at other events for those in the education community and for senior managers and policy makers in education (Morrison and Secker, 2020). They launched a webinar series, to help support the community and build confidence in answering challenging copyright queries. These webinars became an ongoing event featuring a number of guest presenters from national and international organisations such as Harvard University and Creative Commons. Many of the webinars were open to all and included contributions from a range of different people, including those representing copyright owners and legal academics providing the community with expert guidance (Hudson and Wragg, 2020). However, some sessions were closed to allow the community to discuss sensitive issues related the interpretation of copyright law. In autumn 2020, the speakers decided to set up a special interest group in Copyright and Online Learning as part of the Association of Learning Technology. This was intended to provide the community with a sustainable basis on which to continue the webinars and build on the work already done to draw together different perspectives. The crisis meant that despite not being able to travel, there were in fact more opportunities to speak to groups about copyright outside of the UK. The speakers presented at events in New Zealand, Jamaica and Switzerland, to name just a few countries, and it became clear that copyright issues were affecting educators worldwide. The speakers will conclude by describing their future plans, and reflect on what the pandemic has taught them about the need for ongoing community support to develop confidence and resilience in the education sector. They will also discuss the creative ways they have devised to continue working and teaching others about copyright. Finally, Chris and Jane will share their commitment to advocating for copyright literacy as an essential part of solving the challenges the education community is facing.